Construct Validity of the Athlete Introductory Movement Screen in Grassroots Footballers Aged 11-13 Years - Michael J Duncan; Matteo Crotti; Ricardo Martins; Lucas Guimaraes-Ferreira; Jason Tallis; William Pattison (MDPI AG, 2024)
Background: This study examined the construct validity of the Athlete Introductory Movement Screen (AIMS) in children. Methods: Following ethics approval, parental consent, and child assent, 87 children (50 boys, 37 girls) aged 11-13 years (Mean ± SD = 12.4 ± 0.6 years) performed the AIMS and Test of Gross Motor Development (TGMD-3) in a counterbalanced order. AIMS tertiles were subsequently created, classifying children with 'high', 'medium', or 'low' movement skills. Results: A 2 (Gender) X 3 (AIMS tertile) ways analysis of covariance (ANCOVA), controlling for age and age at peak height velocity, with TGMD-3 scores as the dependant variable, indicated that TGMD-3 scores were significantly higher for girls categorised as having a medium movement skill compared to girls categorised as low, and those categorised having high movement skill compared to medium and low movement skill groups (all, p = 0.001). There was no difference in TGMD-3 scores for boys classed as having low and medium movement skills. Boys categorised as high for movement skills had significantly greater TGMD-3 scores than their peers categorised as having both low and medium movement skills (p = 0.001). Conclusions: As the AIMS differentiates the theoretically related construct of motor competence, this study demonstrates that the AIMS has construct validity as a measure of movement skill in children aged 11-13 years.